Optimization of microwave-assisted extraction for quercetin (prebiotic) and the effect of its symbiotic combination with Lactobacillus acidophilus (probiotic) in NAFLD induced rat model - Majeed, Mehwish; Ahmed, Waqas; Javad, Sumera; Iahtisham-Ul-Haq,; Rashid, Summer; Perveen, Rashida; Farooq, Umar; Abid, Juweria; Ahmad, Abdul Momin Rizwan (Frontiers in Nutrition, 2025)
IntroductionChanging dietary patterns, lifestyle related disorders and associated metabolic syndromes have increased the prevalence of NAFLD over the last few years. It has been observed that there is a direct association between intestinal dysbiosis and NAFLD truly depicted by interconnected complex mechanisms. Besides its antioxidant activity, quercetin serves prebiotic functions as well.ObjectiveThe objective of the current research was to determine the synbiotic effect of quercetin and Lactobacillus acidophilus on non-alcoholic fatty liver disease (NAFLD) induced rat models.MethodsQuercetin was extracted from red onions via microwave-assisted extraction technique (MAE). Response Surface Methodology (RSM) was employed to optimize MAE parameters. 25 female albino rats were divided into 5 groups of 5 rats each; 2 control (untreated and negative control) and 3 treatment groups (G1, G2, G3). High fat diet (HFD) (40% fat) in combination with 15% sucrose water and 440 mg cholesterol/100 g feed was given to rats over a period of 6 weeks to induce NAFLD. For the efficacy trial, treatment groups received different doses of quercetin; 50 mg, 80 mg and 100 mg in G1, G2 and G3, respectively, with a dose of 102 CFU of Lactobacillus acidophilus/200 μL of PBS in all three groups.ResultsThe results revealed optimal MAE conditions for maximum amount of quercetin as 600 W microwave power, 3 min irradiation time and distilled water as a solvent. Resultantly, 86.10 mg quercetin/gram of red onion extract (32.7mgQ/g onion powder) was obtained. There was no significant difference in HDL, VLDL, triglycerides, serum AST and serum ALP levels (p-value > 0.05) between all groups. However, total cholesterol, LDL cholesterol and serum ALT significantly improved in G3 (p-value < 0.05).ConclusionThe synbiotic combination is effective at lowering total cholesterol, LDL cholesterol as well as serum ALT levels at a dose of 100 mg of quercetin/kg body weight for rats.